2013
DOI: 10.1186/1472-6874-13-5
|View full text |Cite
|
Sign up to set email alerts
|

Unmarried women’s ways of facing single motherhood in Sri Lanka – a qualitative interview study

Abstract: BackgroundIn Sri Lanka, motherhood within marriage is highly valued. Sex out of wedlock is socially unacceptable and can create serious public health problems such as illegal abortions, suicide and infanticide, and single motherhood as a result of premarital sex is considered shameful. The way unmarried women facing single motherhood reflect on and make use of their agency in their social environments characterised by limited social and financial support has consequences for the health and well-being of both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…Abortion seekers in Colombo revealed that seeking abortion was in conflict with their personal will and moral ideals, but it was carried out to protect their own and their families' reputation (Olsson & Wijewardena, 2010). Infanticide and suicide (Jordal et al, 2013;Marecek, 2006) are other routes for unmarried women to escape disclosure of premarital sex and minimize the damage to their respectability.…”
Section: Symbolic Dimensionsmentioning
confidence: 97%
See 2 more Smart Citations
“…Abortion seekers in Colombo revealed that seeking abortion was in conflict with their personal will and moral ideals, but it was carried out to protect their own and their families' reputation (Olsson & Wijewardena, 2010). Infanticide and suicide (Jordal et al, 2013;Marecek, 2006) are other routes for unmarried women to escape disclosure of premarital sex and minimize the damage to their respectability.…”
Section: Symbolic Dimensionsmentioning
confidence: 97%
“…The contradictions between the symbolic values of respectability and the emotional values of romance and intimacy constitute a detrimental SRHR risk for the migrant women. Difficulties in handling these contradictions are likely to contribute to unwanted pregnancies, illegal and unsafe abortions (Thalagala, 2010), unwanted adoptions or stigmatized motherhood (Jordal et al, 2013), infanticide (Jayasinghe, 2012), or suicide (Marecek, 2006).…”
Section: Emotional Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The goals of these researcher included profiling children with mental health problems, to identify related disparities, and to quantify the identification of family burdens. Jordal M et al [21] Unmarried women's ways of facing single motherhood in Sri Lanka -a qualitative interview study.…”
Section: Outcome(s)mentioning
confidence: 99%
“…Respectability for Sri Lankan women's social acceptance and economic survival is essential and has been demonstrated in several studies (Ruwanpura 2006;Hewamanne 2007;Olsson and Wijewardena 2010;Jordal, Wijewardena, and Olsson 2013). It also plays a role in marginalised women's negotiation of SRHR (Jordal et al 2014).…”
Section: Introductionmentioning
confidence: 97%